The knowledge of parents with infants and toddlers for antibiotic consumption - Munkhjargal, Gan-Undral; Yadmaa, Unurjargal; Yadmaa, Unurjargal; Tsolmon, Lkhagvasuren; Baasan, Munkhdelger; Sharavdorj, Oyunbileg; Ganbold, Tserenchunt; Zundui, Ariunaa (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Antibiotics are commonly prescribed in paediatrics. Children were 1.30 times more likely to be treated with antibiotics compared to adults3. Especially, antibiotic prescription is higher in children aged under 5 years. The survey was conducted in a cross-sectional survey design using the questionnaire used in India. The questionnaire were used for scoring KAP. Participants were confused regarding the indication of antibiotics use. This is indicated from the fact that only 173 parents (41.4%) were aware that antibiotics are used against bacterial infection, while 119 parents (28.5%) incorrectly thought that they are used against viruses and 112 parents (26.8%) felt that antibiotics could be used for any microorganism. Concerning the reason of use of antibiotics, majority (n=186) of the parents gave it to the child for cough and cold, followed next by fever (n=169). According to the KAP assessment of the parents who participated in the survey, there were 20 with poor knowledge, 168 with medium knowledge, and 230 with good knowledge. More than half (55.0%) of 418 parents have good or sufficient knowledge of the appropriate use of antibiotics, and the rest (45.0%) have medium and low knowledge or insufficient knowledge.